2021
DOI: 10.15421/022152
|View full text |Cite
|
Sign up to set email alerts
|

Influence of metal nanocarboxylates and different water supply conditions on efficiency of soybean-rhizobial symbiotic systems

Abstract: Insufficient water supply is one of the main factors that significantly reduce the activity of nitrogen fixation by legume-rhizobial symbiotic systems. That is why comprehensive research on aspects of their resistance to water stress and the search for scientifically substantiated ways to improve the existing ones and develop modern, competitive technologies of growing legumes in arid conditions are becoming especially relevant. The aim of the work was to investigate the processes of formation and functioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…An important factor that significantly reduces the "nitrogen fixation activity of legume-rhizobial symbiotic systems" is insufficient water supply (Kots et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…An important factor that significantly reduces the "nitrogen fixation activity of legume-rhizobial symbiotic systems" is insufficient water supply (Kots et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, it should be noted that the effectiveness of the combined use of technologies for seed inoculation with rhizobia and priming with nano preparation of various metals to increase the resistance of legumes to drought almost has not been studied. Kots et al (2021) have investigated and discussed possible mechanisms of various nanometal carboxylates (NMC) effects on rhizobia and soybean seeds treated with them at the formation of symbiotic systems parameters (nodules number and mass, their nitrogen-fixing activity) under conditions of optimal and insufficient water supply. It was shown that carboxylates of nano-Ge, nano-Co and nano-Fe exhibited the most pronounced protective effect, which enhanced the rhizobia nodulation activity, fixation of molecular nitrogen by soybean symbiotic systems under insufficient water supply, and stimulated their recovery after stressor cessation.…”
mentioning
confidence: 99%